High Risk of Further Surgery After Radial Head Replacement for Unstable Fractures: Longer-term Outcomes at a Minimum Follow-up of 8 Years. Issue 11 (November 2019) - Cristofaro, Caroline D.; Carter, Thomas H.; Wickramasinghe, Neil R.; McQueen, Margaret M.; White, Timothy O.; Duckworth, Andrew D.
Abstract: Background: The evidence for treating acute, unreconstructable radial head fractures in unstable elbows with radial head replacement predominantly consists of short- to mid-term follow-up studies with a heterogenous mix of implants and operative techniques. Data on longer-term patient-reported outcomes after radial head replacement is lacking. Questions/purposes: (1) What proportion of patients undergo revision or implant removal after radial head replacement? (2) At a minimum of 8 years follow-up, what are the patient-reported outcomes (QuickDASH, Oxford Elbow Score, and EuroQol-5D)? (3) What factors are associated with a superior long-term patient-reported outcome, according to the QuickDASH? Methods: Between September 1994 and September 2010, we surgically treated 157 patients for acute radial head fractures. We excluded patients where the radial head was excised (n = 21), internally fixed (n = 15), or replaced as a secondary procedure after failed internal fixation (n = 2). A total of 119 patients who underwent radial head replacement surgery for an acute unreconstructable fracture were included, with a mean age of 50 years (range 15 to 93 ± 19 years), and 53% of patients (63) were women. All but two implants were uncemented, loose-fitting, monopolar prostheses, of which 86% (102) were metallic and 14% (17) were silastic. Implants were only cemented if they appeared unstable within the proximal radius. Silastic implants were used in the earlier series and replaced by metallic implants starting in 2000. We reviewed electronic records to document postoperative complications and prosthesis revision and removal. A member of the local research team (THC, CDC) who was not previously involved in patient care contacted patients to confirm complications, reoperations and to obtain long-term patient-reported outcomes scores. Nineteen patients had died at the point of outcome score collection. Of the remaining 100 patients, 80 were contacted (67% of total cohort), at a median of 11 years (range 8 to 24 years) after injury. The primary outcome measure was the QuickDASH score. Results: Of 119 patients, 25% (30) underwent reoperation, with three patients undergoing revision and 27 patients undergoing prosthesis removal at a median of 7 months (range 0 to 125 months). Twenty-one of 30 procedures (70%) occurred within 1 year after implantation. Kaplan-Meier survivorship analysis demonstrated a cumulative implant survival rate of 71%. In the 80 patients contacted, the mean QuickDASH score was 13 ± 14, the mean Oxford Elbow Score was 43 ± 6, and the median EuroQol-5D score was 0.8 (-0.3 to 1.0). After controlling for covariates, we found that prothesis revision or removal (p = 0.466) and prosthesis type (p = 0.553) were not associated with patient-reported outcome, according to the QuickDASH. Conclusions: The management of acute unreconstructable fractures of the radial head in unstable elbow injuries with radial head replacement has a high risk of reoperation. Patients must be counselled regarding this risk of secondary intervention, of which the peak risk appears to be within 1 year after implantation. Despite this, patients report low disability according to the QuickDASH at a minimum follow-up of 8 years. Level of Evidence: Level IV, therapeutic study.